Basal Cytokeratin Phenotypes of Myoepithelial Cells Indicates the Origin of Ductal Carcinomas In Situ of the Breast. Issue 8 (September 2015) - Chen, Ling; Yin, Xiaona; Lu, Shanshan; Chen, Guorong; Dong, Lei
<x xml:space="preserve">Abstract</x> Terminal duct lobular unit (TDLU) is widely accepted as the origin of ductal carcinoma in situ of breast. The differentiation states of myoepithelial cells of breast ductal system hint the development of breast hyperplastic lesions. Basal cytokeratin (CK) phenotypes indicate the differentiation of myoepithelial cells. Using antibodies of CK5/6, CK14, and CK17, this study reports the basal CK phenotypes of myoepithelial cells in 20 foci of normal breast, 20 usual ductal hyperplasias, 36 ductal carcinomas in situ (DCIS), and 28 sclerosing adenosis (SA). The results showed that the positive staining of basal CKs of myoepithelial cells in normal ducts were significantly higher than those in normal lobules. The basal CK expression of myoepithelial cells of DCIS and usual ductal hyperplasia was similar to that of normal duct, whereas that of SA was similar to that of normal lobule. We propose a modified model of TDLU origin of intraductal carcinoma that most of DCIS originate from terminal ducts of TDLU, whereas most SA originate from lobules.